Предмет: Алгебра,
автор: alenatalygina
Представте в виде квадрата двучлена выражение: 9а² - 6a +1
Решите уравение:a)6 - х(х+1)+9 -х²
б)6(х-2)=7х-(3х+1)
ПОМОГИТЕЕЕ
Ответы
Автор ответа:
0
1) 9a²-6a+1=(3a-1)²
3) 6(x-2)=7x-(3x+1)=
6x-12=7x-3x-1
6x-12=4x-1
6x-4x=-1+12
2x=11
x=11/2
3) 6(x-2)=7x-(3x+1)=
6x-12=7x-3x-1
6x-12=4x-1
6x-4x=-1+12
2x=11
x=11/2
Похожие вопросы
Предмет: Математика,
автор: kxbestfriends
Предмет: Русский язык,
автор: ivanovaveronika396
Предмет: Литература,
автор: korobzoa10
Предмет: Алгебра,
автор: dashamarkus1232
Предмет: Химия,
автор: tselousov2001